PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA DOSEN ( STUDI PADA YAYASAN PENDIDIKAN PERSADA BUNDA PEKANBARU ) - BASRIANI, AGUSTIN (Jurnal Tepak Manajemen Bisnis, 2016)
The Effect of Competence and Organization Commitment on Job Satisfaction and Lecturer Performance (Study on Yayasan Pendidikan Persada Bunda Pekanbaru). One of educational goals is to create qualified human in the future, therefore the role of institution of higher education is needed very much. To produce qualified graduates, of course the colleges should have to be qualified ones. The quality of education is affected by several factors such as: students, infrastructure facilities supporting the learning process, and lecturers.This study aims to determine the effect of Competence and Organization Commitment on Job Satisfaction and Lecturer Performance (Case Study on Yayasan Pendidikan Persada Bunda Pekanbaru). The sampling technique used in this research is saturated sampling technique, while the sample is all permanent lecturers of Yayasan Pendidikan Persada Bunda Pekanbaru. There are 61 permanent lecturers there. For technique of Data Collection, the researcher applied questionnaire, interview, and documentation. While in techniques of Data Analysis the researcher used multiple linear regression analysis and simple linear regression which were continued to be analyzed by using SPSS version 21.0. The results of this research showed both partially and jointly of Competence and Organization Commitment were affected each other on lecturer job satisfaction. Meanwhile the variable of job satisfaction partially affected the lecturer performance.